1980
DOI: 10.1161/01.str.11.6.629
|View full text |Cite
|
Sign up to set email alerts
|

"Low perfusion hyperemia" following middle cerebral arterial occlusion in cats of different age groups.

Abstract: SUMMARY Thirty-one cats were divided by age into 3 groups, young (Y), middle (M) and old (O). Continuous recordings of local cerebral blood volume (CBV) and frequent measurements of mean transit time of blood (I) were made from the Sylvian opercula after ischemia was produced by transorbital clipping of the middle cerebral artery at its origin (MCA occlusion). Control recordings were made simultaneously from the corresponding area of the contralateral cerebral hemisphere.MCA occlusion temporarily stopped cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…17 In their study, a raised CBV measured within 6 to 48 hours of stroke onset did not contribute to maintaining metabolic activity in the peri-infarct regions. Tomita et al 34 found "low-perfusion hyperemia" in the ischemia model of cat brain, which followed the initial CBV decrease immediately after MCA occlusion and disappeared within several hours. The low-perfusion hyperemia did not have a protective effect on ischemic lesion evolution.…”
Section: Discussionmentioning
confidence: 99%
“…17 In their study, a raised CBV measured within 6 to 48 hours of stroke onset did not contribute to maintaining metabolic activity in the peri-infarct regions. Tomita et al 34 found "low-perfusion hyperemia" in the ischemia model of cat brain, which followed the initial CBV decrease immediately after MCA occlusion and disappeared within several hours. The low-perfusion hyperemia did not have a protective effect on ischemic lesion evolution.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic standpoint, robust collaterals are a potent predictor of arterial recanalization, preserved tissue fate, and good clinical outcomes in acute stroke. Although much emphasis has been placed on specific arterial collateral routes that bypass flow around occlusions, the capacity of other elements such as the venous system to maintain cerebral blood volume remains essential (Tomita et al, 1980). Even when seemingly equivalent cases of proximal middle cerebral artery (MCA) occlusion are compared, the underlying etiology or mechanism such as atherosclerotic plaque or thromboembolism culminating in occlusion has a striking effect on ischemic severity (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Global and focal models have suggested that volume-flow mismatch (ie, high or preserved CBV with low CBF) may be a feature of early ischemia 16 -19 and represent tissue at risk of infarction. 16,20,21 Such regions have been observed in humans and tend to progress to infarction without intervention. 20,22 Steady-state susceptibility contrast MRI measurements of relative regional CBV provide a unique combination of high sensitivity, accuracy for measurement of CBV changes, and high temporal resolution for in vivo studies.…”
mentioning
confidence: 99%